Palladium-Catalyzed Carbonyl Allylation Reactions Using Tin Chloride: A Mini-Review - Guidote, Armando M, Jr (Archīum Ateneo, 2018)
The treatment of allylic alcohols as synthons of carbanions for carbonyl allylation reactions in the presence of a Pd-SnCl2 system has been one of the most interesting and most useful developments demonstrated by Yoshiro Masuyama and co-workers in the field of organic synthesis. The reaction makes use of palladium as an effective catalyst and tin (II) chloride as a low-valent reducing agent which also effectively transforms the allylic group to a nucleophilic group. The organic, as well as organometallic, chemistry of how the transformations occur and how the metals take part in the reaction is of great interest. These could help allow for better optimization of reagents and solvents, for better control of the extent of reaction or yield of desired product, and for possible applications in other reaction systems. This review will focus primarily on the work of Yoshiro Masuyama and various co-workers on carbonyl allylation reactions making use of a Pd-SnCl2 system or substitutes thereof.